Optical coherence tomography evaluation of retinal nerve fiber layer in longitudinally extensive transverse myelitis - Frederico C. Moura; Danilo B. Fernandes; Samira L. Apóstolos-Pereira; Dagoberto Callegaro; Paulo E. Marchiori; Mário L.R. Monteiro (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To compare optical coherence tomography (OCT) measurements on the retinal nerve fiber layer (RNFL) of healthy controls and patients with longitudinally extensive transverse myelitis (LETM) without previous optic neuritis. METHOD: Twenty-six eyes from 26 patients with LETM and 26 control eyes were subjected to automated perimetry and OCT for comparison of RNFL measurements. RESULTS: The mean deviation values from perimetry were significantly lower in patients with LETM than in controls (p<0.0001). RNFL measurements in the nasal quadrant and in the 3-o'clock segment were significantly smaller in LETM eyes than in controls. (p=0.04 and p=0.006, respectively). No significantly differences in other RNFL measurements were found. CONCLUSION: Patients with LETM may present localized RNFL loss, particularly on the nasal side of the optic disc, associated with slight visual field defects, even in the absence of previous episodes of optic neuritis. These findings emphasize the fact that patients with LETM may experience attacks of subclinical optic nerve damage.